Pengembangan Bahan Ajar Bahasa Indonesia pada Materi Puisi Berbasis Kearifan Lokal Kota Tanjung Balai pada Kelas V SD Negeri 137957 TA 2024/2025 - Yulanda Fathira Simamora; Eva Betty Simanjuntak; Apiek Gandamana; Edizal Hatmi; Dody F. Pandimun Ambarita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study reveals how difficult it is to teach poetry appreciation to students. The research used in this study is research and development (R&D). The subjects in this development research were 30 fifth-grade students of SD Negeri 137957 Tanjungbalai in the 2024/2025 Academic Year. While the object of this research and development is the Indonesian Language module based on local wisdom of Tanjungbalai city on poetry material for fifth-grade elementary school. The data collection technique for this study used interviews, questionnaires, and tests. The analysis technique of this study tested the validity analysis module, and the effectiveness analysis of the module. Based on the results of the study, it was concluded that simple teaching materials based on local wisdom in Indonesian Language learning chapter 10 topic b